2014
DOI: 10.1007/s11240-014-0436-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from leaf-derived protoplasts within the Daucus genus: effect of different conditions in alginate embedding and phytosulfokine application

Abstract: Protoplasts of four Daucus carota subspecies and three wild Daucus species were isolated from 2-weekold shoot cultures during overnight incubation in an enzyme mixture composed of 1 % (w/v) cellulase Onozuka R-10 and 0.1 % (w/v) pectolyase Y-23. Before the culture, they were embedded in autoclave-or filter-sterilized alginate solution. Modified thin alginate layer (TAL) and extra thin alginate film (ETAF) techniques were applied for protoplast immobilization. A rich mineral-organic medium based on the formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 63 publications
(97 reference statements)
5
47
0
Order By: Relevance
“…Hypocotyl elongation and root growth are promoted by PSK, mainly through the signaling of cell elongation rather than cell division [26,27]. However, in suspension cultures PSK promotes the proliferation of cells of both monocot and dicot plants [23,28,31,32] and due to this feature, phytosulfokine-α has been proposed as a candidate to supplementing plant in vitro cultures together with other well-known plant growth regulators [40,41]. These results were the assumption to perform our experiments.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hypocotyl elongation and root growth are promoted by PSK, mainly through the signaling of cell elongation rather than cell division [26,27]. However, in suspension cultures PSK promotes the proliferation of cells of both monocot and dicot plants [23,28,31,32] and due to this feature, phytosulfokine-α has been proposed as a candidate to supplementing plant in vitro cultures together with other well-known plant growth regulators [40,41]. These results were the assumption to perform our experiments.…”
Section: Discussionmentioning
confidence: 83%
“…The authors demonstrated that application of exogenous PSK reversed the recalcitrance of in vitro cultured mesophyll sugar beet cells. Recently, Maćkowska et al [41] cultured protoplasts of different Daucus accessions in the presence of PSK. Their results showed that in five out of seven tested accessions, PSK-α at a concentration of 100 nM (0.1 µM) led to an increase in plating efficiency (55-80%) in comparison with the control (40-65%).…”
Section: Discussionmentioning
confidence: 99%
“…Further work has led to the development of thin alginate layers (TAL), successfully used in Arabidopsis, Nicotiana, Daucus and Beta (Dovzhenko et al, 1998;Dovzhenko et al, 2003;Maćkowska et al, 2014), and extra-thin alginate film (ETAF) used in Rosa sp. (Pati et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare the effects of alginate sterilization method on protoplast culture, since the cited studies use different species, embedding techniques (layers/beads) and culture media, all of which affect the results. Maćkowska et al (2014) compared the two methods of alginate sterilization for protoplast embedding in cultivated and wild carrots. They showed a positive effect of alginate filter-sterilization on protoplast plating efficiency but the effect was also strongly genotype-dependant.…”
Section: Discussionmentioning
confidence: 99%
“…Protoplast systems are the most suited for rapid screening of gene silencing (siRNA and miRNA) and genomeediting (e.g. CRISPR) targets (Cao et al, 2014;Maćkowska et al, 2014;Schapire and Lois, 2016;You et al, 2014;Zhai et al, 2009). In addition, protoplast-based systems are now available for almost any plant of commercial interest, including lettuce (Lactuca sativa) (Sasamoto and Ashihara, 2014), grape (Vitis vinifera) (Wang et al, 2015) and bean (Phaseolus vulgaris) (Nanjareddy et al, 2016) and even the less expected, such as oil palm (Elaeis guineensis) (Masani et al, 2014), poplar (Populus euphratica) (Guo et al, 2015) and switchgrass (Panicum virgatum) (Burris et al, 2016).…”
Section: Highlight On Abi3 As a New Major Lead For Improvement On Lipmentioning
confidence: 99%